2016
DOI: 10.19175/recom.v6i3.758
|View full text |Cite
|
Sign up to set email alerts
|

Uma reflexão sobre o manejo familiar da criança com doença falciforme

Abstract: RESUMOObjetivo: suscitar uma breve reflexão acerca de elementos que envolvem o manejo familiar da criança com doença falciforme. Método: trata-se de uma reflexão teórica, com revisão de literatura para respaldar as questões norteadoras: o que é manejo familiar e quais são os seus principais aspectos que norteiam a assistência voltada à criança nesta condição? Os artigos selecionados foram analisados segundo a técnica de análise textual, surgindo duas categorias: "Impacto da doença crônica na criança e família"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
3
0
9
Order By: Relevance
“…In fact, initially, the news of being an "incurable" disease generates a phase of denial and despair, which is gradually faced by experience with the disease. However, it is always a difficult process, requiring great emotional balance (16) . Thus, at the time of reporting on the disease, health professionals need to pay attention to families' longing, which often expect attention to their psychic suffering, and offer emotional support compatible with their real needs at that moment (17) .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, initially, the news of being an "incurable" disease generates a phase of denial and despair, which is gradually faced by experience with the disease. However, it is always a difficult process, requiring great emotional balance (16) . Thus, at the time of reporting on the disease, health professionals need to pay attention to families' longing, which often expect attention to their psychic suffering, and offer emotional support compatible with their real needs at that moment (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Assim sendo, as hospitalizações de repetição, em que a família vivencia os procedimentos invasivos na criança como as venopunções e administrações de medicamentos, geram o sofrimento e o medo da perda do filho (Gesteira;Bousso & Rodarte, 2016).…”
Section: Assistência Terapêuticaunclassified
“…7 When symptoms and treatment begin, the family can better understand the severity of the disease and the need for intensive health care, and the importance of receiving appropriate guidelines for the prevention of complications in the child's body. 8 However, national and international literature has revealed that many family members and caregivers have had low knowledge about sickle cell disease, its pathophysiology, genetic inheritance, complications, necessary care, among other information. [9][10][11][12] From this perspective, it is pointed out that health education aims to promote self-care in people with sickle cell disease; when infants, this care is linked to the relatives, because these people are dependent on others with greater age and knowledge.…”
Section: Introductionmentioning
confidence: 99%